Roadmap for integrating blockchain with Internet of Things (IoT) for sustainable and secured operations in logistics and supply chains: Decision making framework with case illustration - Kumar, Devinder; Singh, Rajesh Kr; Mishra, Ruchi; Daim, Tugrul U. (ELSEVIER SCIENCE INC, 2023)
Blockchain and Internet of Things (IoT) technologies have considerable potential to achieve sustainability in logistics and supply chain management. However, the integration of blockchain-IoT has not been explored extensively in past research. This research provides a complete analysis of the enablers for using blockchain-IoT to manage logistics and supply chains. It aims to explore and prioritise various enablers for its adoption. The Diffusion of Innovation and the Technology-Organisation-Environment theories are used in this research to examine blockchain-IoT adoption enablers. The enablers identification is confirmed using the Fuzzy-Delphi technique and then analysed using the fuzzy - Decision-Making Trial and Evaluation Laboratory tool to determine the strength of cause-effect hierarchical framework. The sensitivity analysis is also carried out to address the robustness of the results obtained. In order to measure the extent of a firm's readiness to adopt blockchainIoT, a framework based on Graph Theory Matrix Method is proposed. It is illustrated with the help of a real life case. The results revealed that 'sustainability focus', 'emphasis on emerging technology by organisation', and 'technology maturity' are the top three enablers for blockchain-IoT adoption. Findings of study may motivate managers to include blockchain-IoT into their strategic planning processes based on their categorization of enablers into cause and effect categories. The research findings may also be used to the creation of efficient Blockchain-IoT deployment methods.
Keywords: Blockchain; IoT; Fuzzy Delphi; Fuzzy DEMATEL; Graph Theory Matrix Approach (GTMA); Collaborative decision making; Technology-Organisation-Environment (TOE); Diffusions-of-innovation (DOI); DELPHI METHOD; BIG DATA; MANAGEMENT; TECHNOLOGY; ADOPTION; PERSPECTIVE; PERFORMANCE; ACCEPTANCE; IMPACT; RISKS; Business & Economics; Public Administration